Assessment of insulin like growth factor 1 and bone density in normal and ?-thalassemia major children - Sohail, Hira; Ijaz, Farhat; Malik, Aaminah; Kamran, Rizwana; Javed, Sahar; Aftab, Rana Khurram (Pakistan Journal of Physiology, 2019)
Background: Hepcidin production is affected by multiple stimuli including iron status of the body, erythropoiesis, hypoxia and inflammatory conditions. This study was conducted to assess the effect of maternal hepcidin concentration on the different modes of delivery and maternal age groups. Cord blood hepcidin was also compared with neonatal gender. Methodology: The present study is observational type and conducted in Baqai Medical University from Sep 2015 to Mar 2016. To carry out the study, 25 healthy full-term pregnant females were included along with the cord blood samples. Five (5) ml blood was drawn from females and infants. Serum hepcidin were measured in both mothers and cord blood by using ELISA. Kruksal Wallace test was performed to observe the difference in hepcidin levels in females with different modes of delivery and with different age groups. Difference in neonatal hepcidin on the basis of gender was analyzed by Mann Whitney U test. Results: There was no significant difference between the maternal hepcidin values who delivered vaginally or underwent emergency or elective caesarean sections (p=0.871); however maternal age showed significant difference with maternal hepcidin (p=0.022). Neonatal hepcidin value did not vary on the basis of gender (p=0.475). Conclusion: Mode of delivery is independent of maternal and neonatal hepcidin levels. There were no differences gender-wise, whereas maternal age had effects on hepcidin levels of women.